Estimating the probability distributions of radioactive concrete in the building stock using Bayesian networks. (15th July 2023) - Wu, Pei-Yu; Johansson, Tim; Mangold, Mikael; Sandels, Claes; Mjörnell, Kristina
Graphical abstract: Highlights: Learning Bayesian networks identify the presence pattern of in situ blue concrete. Indoor radon measurements and environmental inventories are used for modeling. Conditional probability and causal relationship of radioactive concrete are computed. Predictive inference estimates the presence of radioactive concrete in buildings. The method can advise risk-based inspection in potentially contaminated buildings. Abstract: The undesirable legacy of radioactive concrete (blue concrete) in post-war dwellings contributes to increased indoor radon levels and health threats to occupants. Despite continuous decontamination efforts, blue concrete still remains in the Swedish building stock due to low traceability as the consequence of lacking systematic documentation in technical descriptions and drawings and resource-demanding large-scaled radiation screening. The paper aims to explore the predictive inference potential of learning Bayesian networks for evaluating the presence probability of blue concrete. By integrating blue concrete records from indoor radon measurements, pre-demolition audit inventories, and building registers, it is possible to estimate buildings with high probabilities of containing blue concrete and encode the dependent relationships between variables. The findings show that blue concrete is estimated to be present in more than 30% of existing buildings, more than the current expert assumptions of 18–20%. The probability of detecting blue concrete depends on the distance to historical blue concrete manufacturing plants, building class, and construction year, but it is independent of floor area and basements. Multifamily houses and buildings built between 1960 and 1968 or nearby manufacturing plants are more likely to contain blue concrete. Despite heuristic, the data-driven approach offers an overview of the extent and the probability distribution of blue concrete-prone buildings in the regional building stock. The paper contributes to method development for pattern identification for hazardous building materials, i.e., blue concrete, and the trained models can be used for risk-based inspection planning before renovation and selective demolition.